Improved Bioactivity of 3D Printed Porous Titanium Alloy Scaffold with Chitosan/Magnesium-Calcium Silicate Composite for Orthopaedic Applications - Tsai, Chun-Hao; Hung, Chih-Hung; Kuo, Che-Nan; Chen, Cheng-Yu; Peng, Yu-Ning; Shie, Ming-You (Materials, 2019)
Recently, cases of bone defects have been increasing incrementally. Thus, repair or replacement of bone defects is gradually becoming a huge problem for orthopaedic surgeons. Three-dimensional (3D) scaffolds have since emerged as a potential candidate for bone replacement, of which titanium (Ti) alloys are one of the most promising candidates among the metal alloys due to their low cytotoxicity and mechanical properties. However, bioactivity remains a problem for metal alloys, which can be enhanced using simple immersion techniques to coat bioactive compounds onto the surface of Ti–6Al–4V scaffolds. In our study, we fabricated magnesium-calcium silicate (Mg–CS) and chitosan (CH) compounds onto Ti–6Al–4V scaffolds. Characterization of these surface-modified scaffolds involved an assessment of physicochemical properties as well as mechanical testing. Adhesion, proliferation, and growth of human Wharton’s Jelly mesenchymal stem cells (WJMSCs) were assessed in vitro. In addition, the cell attachment morphology was examined using scanning electron microscopy to assess adhesion qualities. Osteogenic and mineralization assays were conducted to assess osteogenic expression. In conclusion, the Mg–CS/CH coated Ti–6Al–4V scaffolds were able to exhibit and retain pore sizes and their original morphologies and architectures, which significantly affected subsequent hard tissue regeneration. In addition, the surface was shown to be hydrophilic after modification and showed mechanical strength comparable to natural bone. Not only were our modified scaffolds able to match the mechanical properties of natural bone, it was also found that such modifications enhanced cellular behavior such as adhesion, proliferation, and differentiation, which led to enhanced osteogenesis and mineralization downstream. In vivo results indicated that Mg–CS/CH coated Ti–6Al–4V enhances the bone regeneration and ingrowth at the critical size bone defects of rabbits. These results indicated that the proposed Mg–CS/CH coated Ti–6Al–4V scaffolds exhibited a favorable, inducive micro-environment that could serve as a promising modification for future bone tissue engineering scaffolds.